ECOPHYSIOLOGICAL RESPONSE OF NERITA ORYZARUM (RECLUZ), A GASTROPOD, TO VARIATIONS IN TEMPERATURE, pH AND SALINITY - Jaiswar, A. K.; Thakur, M. K.; Kulkarni, B. G. (Journal of Indian Fisheries Association, 2015)
During ecophysiological investigations on an intertidal gastropod, Neritaoryzarum (Reduz), of Mumbai shore, various biochemical changes could berecorded. Glycogen and lipid contents of N. oryzarum were found to decrease,whereas, water content increased with decreasing salinity. The rate of oxygenconsumption declined with the decrease in salinity and also in highly acidic(pH 2) as well as highly alkaline (pH 10) sea water. The observed variationsin the rate of oxygen consumption and changes in biochemical compositionin the animal with changes in salinity, pH and temperature are probably theprocess of physiological and biochemical adjustments to the fluctuatingenvironmental conditions in the intertidal region.Key words: Ecophysiology, Nerita oryzarum, oxygen consumption